Evolution Characteristics of New Urbanization in the Provincial Capital Cities of Western China - Zou, Yafeng; Deng, Min; Wang, Qi; Zhang, Qian; Rong, Yao (Frontiers in Environmental Science, 2022)
Urbanization is a concept as well as a project connected with all aspects of the society. China’s urbanization has been attracting wide attention in the world due to its rapid development. The western China is always in a relatively weak developing state compared to the other part of China, but it has large area and giant amount of people, which all require a reasonable urbanization way. In order to show the development level of new urbanization in western China, we constructed an evaluation system and used entropy and weighted summation methods to get the development scores. Then we obtained correlation coefficient by partial correlation analysis method. The results indicate that: 1) Economic, land and social urbanization are the significant influencing factors. 2) Temporal and spatial differences were significant during the 15-year period in the 11 cities. 3) Among the factor layers, the score of social urbanization fluctuated the most, ecological civilization and economic urbanization showed an upward trend, and population urbanization and land urbanization have been relatively stable in past years. 4) For the western capitals, although economic urbanization and ecological civilization have achieved coordinated development in recent years, the endogenous power of the economy still needs to be tapped, and ecological development is facing greater pressure. At the same time, urban land expansion is too fast to respond well to population growth, which also damages the urban ecosystem to a certain extent. This study can provide decision support for the development of new urbanization in the western region.